Evaluasi dan Usulan Perbaikan Situs Web J-PTIIK menggunakan User Experience Questionnaire (UEQ) dan Focus Group Discussion (FGD) - Khoirul Anwar; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Journal of Information Technology and Computer Science Development (J-PTIIK) is one of the journals published by the Faculty of Computer Science (FILKOM) Universitas Brawijaya. J-PTIIK is a scientific journal that focuses on publishing research results of FILKOM students. J-PTIIK has two main functions, namely carrying out the journal publication process and displaying FILKOM student journals. This J-PTIIK website has never undergone a user experience evaluation and it is not known what difficulties the user experiences when it is used. This study focuses on exploring the need for improvement for J-PTIIK. This evaluation uses a quantitative evaluation method in the form of a User Experience Questionnaire (UEQ) and is combined with a qualitative evaluation method using a Focus Group Discussion (FGD). In the problem analysis, the results of the FGD were linked to the Usability aspect contained in the Nielsen Model. Evaluation results can be used to redesign the J-PTIIK interface based on user recommendations. The evaluation results with UEQ are at the normal level for the three scales on UEQ (Attractiveness, Stimulation, and Novelty) which are between -0.8 to 0.8, while the other three scales are at the positive level (Perspicuity, Efficiency, and Dependability) with being above 0.8. Benchmark results show that the UEQ scales all under normal levels, namely at the level below the average (Perspicuity, Efficiency, and Dependability) and the bad level (Attractiveness, Stimulation, and Novelty). From the results of the FGD, there were more problems and negative perceptions from users.